Notarial Deed Cancellation and Legal Liability in Civil Disputes: Pembatalan Akta Notaris dan Tanggung Jawab Hukum dalam Sengketa Perdata - Fahira Safa Chairunnisa; Noor Fatimah Mediawati (Indonesian Journal of Law and Economics Review, 2026)
General Background Notarial deeds serve as authentic legal instruments with strong evidentiary value in civil law systems. Specific Background In practice, notarial deeds may be challenged and annulled by courts, raising questions regarding their legal validity and the responsibility of notaries. Knowledge Gap However, limited studies analyze the legal consequences of deed cancellation and the extent of notary liability based on judicial decisions. Aims This study aims to examine the legal status of canceled notarial deeds and analyze the responsibility of notaries in relation to such annulments. Results The findings indicate that a notarial deed may lose its authenticity and evidentiary strength when annulled by court decisions, and notaries may bear legal responsibility if procedural or substantive errors are proven. Novelty This study highlights the relationship between judicial annulment and the degradation of evidentiary value in notarial deeds within civil disputes. Implications The results suggest the importance of strict compliance with legal procedures and professional standards to prevent disputes and ensure legal certainty in notarial practice. Keywords: Notarial Deed, Legal Liability, Civil Dispute, Authentic Evidence, Deed Cancellation Key Findings Highlights Court rulings may reduce evidentiary strength of authentic documents Liability arises when procedural errors are identified Legal certainty depends on compliance with formal requirements